Trust, Online Reviews, and Ratings as Drivers of Purchase Intention: Evidence from Generation Z Shopee Users in Greater Jakarta - Sylvia Samuel; Daniel Widjaja (Universitas Pelita Harapan, 2025)
E-commerce growth in Indonesia has been accelerated by the rise of platforms such as Shopee, where trust and electronic word of mouth (e-WOM) play critical roles in consumer decision-making. While prior studies have examined reviews, ratings, and trust separately, few have integrated them into a unified model and tested their combined influence among Generation Z consumers. This digitally native cohort dominates online shopping. This study examines the impact of trust, online customer reviews, and online customer ratings on purchase intention, with gender serving as a potential moderator, in the context of Greater Jakarta. Using a quantitative approach and PLS-SEM analysis of survey data from 350 Shopee users, the results reveal that online customer reviews, ratings, and trust significantly and positively affect purchase intention, with online customer ratings exerting the most substantial effect. Unexpectedly, gender and its moderating effects were not significant, suggesting that male and female Gen Z consumers evaluate trust and e-WOM cues similarly. These findings extend the Theory of Planned Behavior and the Elaboration Likelihood Model by demonstrating how central (reviews, trust) and peripheral (ratings) cues jointly influence consumer intentions in an emerging market context. Practically, the study offers actionable implications for platforms and sellers, highlighting the need to strengthen trust-building mechanisms, ensure credible rating systems, and encourage authentic reviews. The research contributes by integrating trust and e-WOM variables into a single model, demonstrating their relevance in Indonesia, and revealing a generational shift in gender differences in online consumer behavior.